Low-Volume Roads with Neat Sand Bases. Issue 1 (January 2015) - Paige-Green, P.; Pinard, M. I.; Netterberg, F.
Vast areas of Southern Africa are covered with surficial sands of Tertiary to Quaternary age. These consist of aeolian sands that are widespread in the western areas of South Africa, Namibia, Botswana, Zimbabwe, and Angola and reach as far north as the Democratic Republic of Congo, as well as coastal and alluvial sands more prevalent in the eastern areas of South Africa, Mozambique, and Tanzania. Many of these sands are extremely thick and blanket most conventional construction materials, which occur only at inaccessible depths beneath them. The sands, consisting mostly of particles within the size range of 0.06 to 2.0 mm, are normally well outside standard base course specifications for roads and are routinely rejected for use. However, experience in several countries has shown that such materials can be successfully used in the upper layers of low-volume road pavements. This finding led to an investigation into the possible specification of sand for use as base; the investigation concluded that the successfully used sands appeared to be restricted to those that were dark red, which is indicative of the presence of significant iron. It was suspected that the iron was possibly producing some form of self-cementation that increased the strength of the sand, making it successful. This paper describes the results of a follow-up investigation in which several sands, including some that were not red but appeared to be successful in road pavement layers, were investigated. Sampling and testing have shown that the aluminum content also appears to have a beneficial effect on the materials and that iron is not necessarily the main contributor to performance. A preliminary test regime and suggested material specification for the use of neat sands as base are introduced.